Analisis Faktor Internal dan Perencanaan SDM pada Pemanfaatkan Tandan Kosong Kelapa Sawit (TKKS) sebagai Bahan Bakar Alternatif - Junaidi, Junaidi; Edi Hamdi; Muhammad Dhafi Iskandar; Dimas Angga Negoro (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This activity analyzes internal factors in the establishment of PT ESP which aims to process Empty Palm Fruit Bunches (EFB) into biomass fuel in the form of pellets, as an alternative renewable energy. This activity explores the technical and economic feasibility of utilizing EFB waste from the palm oil industry for energy production. The use of EFB pellets has proven to be more cost efficient and provides significant environmental benefits, including reducing greenhouse gas emissions compared to the use of conventional coal. In addition, this project supports Indonesia's renewable energy targets and encourages sustainable waste management practices in the palm oil sector. This activity also raises the potential for implementing circular economy principles by converting industrial waste into valuable energy sources. Demand analysis is conducted to understand the factors that influence market demand for certain products. Market demand for renewable energy, especially pellet fuel from Empty Palm Fruit Bunches (EFB), continues to increase along with increasing awareness of the need to reduce carbon emissions and seek more sustainable energy sources. Recommendations include optimizing the supply chain and developing pellet production technology to increase efficiency and ensure the long-term sustainability of this project.